Role of Shamana Chikitsa in The Management of Sthaulya (Obesity) -A Review: Life Sciences-Ayurveda - D. Pardhekar, Dr.Ashvini; Misar Wajpeyi, Dr. Sadhana; Gotarkar, Dr. Shashank (International Journal of Life Science and Pharma Research, 2023)
Sthaulya is Medovaha Strotodusthijanya Vyadhi, which includes abnormal and excessive accumulation of Medodhatu in the body. It is caused by Kapha and Meda aggravating factors like excess intake of Madhur, Snigdha, Guru, Abhishyandi Ahar, and lack of physical activity, and daytime sleep. This results in the aggravation of Kapha and Meda Dhatu leading to Sthaulya. It can be compared with obesity which is a metabolic disorder. According to WHO, rates of overweight and obesity are increasing in both developed and developing countries around the world. Obesity is an illness that can lead to a variety of health problems, including hypertension, coronary artery disease, diabetes mellitus, osteoarthritis, and psychological issues such as stress, anxiety, and depression. In Modern medicine lifestyle modification, Antiobesity drugs and bariatric surgery is indicated as per BMI of patient. All these have some limitations. As most of the individuals noe following the proper lifestyle due to busy schedule. Antiobesity drugs and surgery are associated with adverse effects and expensive. Hence in such scenario Ayurveda formulations can be safely used. So this review is conducted with the aim to study various formulations described in Ayurveda as a Shaman Chikitsa in Sthaulya. The various research articles searched from Google scholar, Ayush Portal on Ayurvedic management of Sthaulya from 2010- 2020 were searched and collected. A total of ten research studies were included in this review. In most of the studies Guggul, Triphala, Guduchi, Musta, Vidanga having Katu, Tikta, Rasa, Ruksha Guna, Kaphamedohar and Lekhana properties are used for the management of Sthaulya. The assessment was done on the basis of BMI, Anthropometric measurement and lipid levels before and after treatment. Significant improvement was found in most of the studies. Sthaulya can be managed effectively with Shamana Chikitsa having Kapha and Medanashaka property.